Evaluation of retina and microvascular changes in the patient with Parkinson’s disease: A systematic review and meta-analysis - Deng, Yu; Jie, Chuanhong; Wang, Jianwei; Liu, Ziqiang; Li, Yuanyuan; Hou, Xiaoyu (Frontiers in Medicine, 2022)
Background: Parkinson's disease (PD) is a multifaceted neurodegenerative disease. The optic nerve, as a window into the central nervous system (CNS), is known to be an important part of the CNS and can be detected non-invasively. With the widespread availability of optical coherence tomography (OCT) devices, an increasing number of studies have paid attention to the neuropathological disorders in the retina of PD patients in recent years. However, it is still controversial whether OCT can be used as a complementary tool for PD diagnosis. Methods: This review is registered with PROSPERO, number CRD42022301258. The Embase, PUBMED, and The Cochrane Library databases were independently retrieved by 2 investigators to identify relevant papers published from 1 January 2017 to 24 January 2022. These studies used OCT or OCTA to evaluate the difference in the retinal nerve fiber layer (RNFL) thickness, ganglion cell layer（GCL) thickness, macula thickness, Cup and disc area superficial retinal capillary plexus (SCP), and deep retinal capillary plexus(DCP). The standard mean difference (SMD) with the 95% confidence interval (CI) was pooled for continuous outcomes. Results: 26 studies had been enrolled in this meta-analysis with a total number of 2790 eyes, including 1343 eyes from the PD group along with 1447 eyes from the HC group. The results revealed that the RNFL thickness (SMD: -0.53; 95%CI, -0.71~-0.35; P < 0.00001), GCL thickness (SMD: -0.43; 95%CI, -0.66 to -0.19; P = 0.0003), macula thickness (SMD: -0.22; 95%CI, -0.22 to -0.11; P ＜0.0001) were significantly thinner in patients with PD. The SCP (SMD: -0.61; 95%CI, -1.31to -0.10; P =0.02) was significantly lower in PD patients. The DCP (SMD: -0.48; 95%CI, -1.02 to -0.06; P =0.08) is lower in PD patients, but the difference was statistically insignificant. Conclusion: RNFL thickness, GCL thickness, macular thickness, and SVD of PD patients are lower than those of healthy control. OCT and OCTA could detect morphological retinal changes in PD and might be objective and reproducible auxiliary tools to assist clinician diagnosis.